Land Banks' Impact on Agrarian Reform and Equitable Land Redistribution - Iswantoro Iswantoro; Resti Dian Luthviati (Faculty of Law, Universitas Pekalongan, 2021)
Agrarian Reform and Land Redistribution have been pursued by the government in various ways. Still, the key question is whether establishing a Land Bank will result in a fair redistribution of land. The purpose of this study is to examine the impact of land banks on agrarian reform and equitable land redistribution following the passage of the Job Creation Act. The findings revealed that the land bank only has a few abandoned lands that are not held by the state, which will be used by the form based on public interest and subsequently handed to the community. The existence of a land bank is a government endeavor to offer land for the public good and for persons who require it.